Social Empowerment Of Pastoral Literacy At STK St. Yakobus Merauke: ODOA Program (One Day One Article) As An Innovative Strategy - Rosmayasinta Makasau; Eko Wahyono; Cyril Njume A (LPPM Universitas PGRI Sumatera Barat, 2024)
This research was triggered by the low of literacy culture and skills of students in pastoral care which impact on the quality of their services to the people. The objectives of this study are: 1) to explain the current condition of pastoral literacy of students at STK St. Yakobus Merauke and 2) present guidelines/ procedures for designing ODOA program implementation activities for pastoral literacy activities. This research uses qualitative method – descriptive approach, using Miles & Huberman (1984) theories in data analysis, namely: data reduction, data presentation and data verification. In-depth interviews were conducted with 10 students of the seventh semester, 4 lecturers who are competent in the pastoral field, and 1 head of UPT Library to obtain the necessary data according to research objectives. The results of the research showed that the condition of the pastoral literacy phase of students is currently in the 3rd position of 6 literacy phases (early literacy, basic literacy, library literacy, media literacy, technological literacy, and visual literacy) literacy initiated by Clay and Fegurson (2001). The 3rd stage or stage in question is the library literacy stage. The pastoral literacy program through the continuous and controlled implementation of ODOA (One Day One Article) is a means to improve students' literacy culture and skills in teaching. The conclusion of the research is by the implementation of ODOA program shows the improvement of students’ pastoral literacy habits and pastoral skills. The novelty of this research is that the presentation of the latest information regarding the position of student’s pastoral literacy stages in South Papua.